2002
DOI: 10.1038/sj.onc.1205148
|View full text |Cite
|
Sign up to set email alerts
|

Activation of STAT5 triggers proliferation and contributes to anti-apoptotic signalling mediated by the oncogenic Xmrk kinase

Abstract: Extensive studies of primary tumors and tumor derived cell lines revealed that inappropriate activation of speci®c STATs (particularly of STAT3 and STAT5) occurs with high frequency in a wide variety of human cancers. We reported recently that the melanoma inducing EGFRrelated receptor Xmrk speci®cally induces constitutive activation of STAT5 in ®sh melanoma cells. However, little is known about the role of STAT5 in solid tumours in general and its function in melanoma in particular. Recent examinations sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 40 publications
(63 reference statements)
2
41
0
Order By: Relevance
“…The results showed a significant increase in the forkhead box O3a (FOXO3a) transcriptional target proapoptotic genes, including Bim (25), FasL (26), and genes involved in cell cycle regulation, including GADD45a (27) and p130, a member of the retinoblastoma family (28) in the T EM subset. Furthermore, the RT-PCR data confi rmed the up-regulation of the survival gene CD27 and the antiapoptotic PIM-2 kinase, with the latter being regulated by the STAT5a cascade in T CM (29). These results validated our gene array data and further suggested the involvement of STAT5a and FOXO3a signaling pathways in mediating the survival of T CM .…”
Section: Functional and Phenotypic Characterization Of Cd4 + T CM Andsupporting
confidence: 76%
“…The results showed a significant increase in the forkhead box O3a (FOXO3a) transcriptional target proapoptotic genes, including Bim (25), FasL (26), and genes involved in cell cycle regulation, including GADD45a (27) and p130, a member of the retinoblastoma family (28) in the T EM subset. Furthermore, the RT-PCR data confi rmed the up-regulation of the survival gene CD27 and the antiapoptotic PIM-2 kinase, with the latter being regulated by the STAT5a cascade in T CM (29). These results validated our gene array data and further suggested the involvement of STAT5a and FOXO3a signaling pathways in mediating the survival of T CM .…”
Section: Functional and Phenotypic Characterization Of Cd4 + T CM Andsupporting
confidence: 76%
“…Costimulation by synergistic growth factors thereby leads to prolongation of MAP kinase activity, which when induced by a single growth factor alone, is almost back to basal level after 90 minutes (Bohm et al, 1995). Activation of the Xmrk kinase when expressed in murine melanocytes leads to complete suppression of melanocyte differentiation, enhanced proliferation, and induction of a transformed phenotype (Wellbrock et al, 2002). In such dedifferentiated cells, MAP kinase activation induced by the receptor was strong and sustained comparable to the situation in fish.…”
Section: Role Of Map Kinase Signalling Inmentioning
confidence: 94%
“…For example, its activation is required for Ros-induced cell transformation, 42 and it also contributes to the mitogenic signaling from the oncogenic Xmrk. 43,44 Studies in chicken B cells suggest that it has a role in proliferation as well as survival Hyperproliferative pathways from truncated G-CSF receptors J Gits et al signaling from the full-length G-CSF-R, 45 whereas others have shown that PI 3-kinase is activated by G-CSF and correlates with inhibition of apoptosis. 14 Furthermore, one of the key signaling molecules downstream of PI 3-kinase, Akt, has been shown to be activated in a sustained manner by truncated G-CSF-Rs.…”
Section: Discussionmentioning
confidence: 99%
“…52 In addition, STAT5 appears to be essential for the myelo-and lymphoproliferative disease induced by TEL-JAK2 fusions, 54 and is also required for cell cycle progression, survival and leukemogenesis induced by BCR-ABL. 55,56 Potential roles in other cancers have also been identified, including melanoma 44 and mammary cancer. 57 By corollary, expression of constitutively active forms of STAT5 has been shown to result in enhanced proliferation of myeloid cell lines 38 and of hematopoietic cells in vivo, 58 which we have recently confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation